PERILAKU HIDUP BERSIH DAN SEHAT KELUARGA PEMULUNG - Raka Galih Sajiwo (UIN Sunan Kalijaga Yogyakarta, 2019)
Every family would want a clean and healthy environment. The level of achieving social welfare can also be passed through behaviors that reflect cleanliness of the environment. This also applies to scavenger families in Babarsari's shanties. In this context, the research was conducted in Babarsari's shanties in the type of field research and was descriptive qualitative in nature. Those who work as scavengers do not recognize clean and healthy living behaviors or PHBS. They are used to environmental life which can be said to not support the survival of their children. An environment full of garbage has become their usual sight. To analyze PHBS, Abraham Maslow's theory of Hirearki's theory of Human Needs is used. The results of this study are that those scavenger families do not have the awareness of the importance of basic needs, such as clean and healthy life behavior or PHBS.Keywords: Social Welfare, Family, Scavenger, Healthy Living Behaviors